Formulasi dan Uji Stabilitas Krim Ekstrak Daun Jambu Mete (Ancardium Ocidentale Linn) - Suci Fitriani; Aprilya Sri Rachmayanti; Reny Haryani (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2021)
This research aims to evaluate the formulation and stability of cashew leaf extract cream (Anacardium occidentale Linn) as the active ingredient. The research method includes cashew leaf sampling, plant identification, leaf preparation, extraction, phytochemical screening, cream preparation, cream evaluation, and physical stability testing. Phytochemical screening results indicate the presence of tannins, flavonoids, and saponins in the cashew leaf extract. The cream formulation of cashew leaf extract was prepared using concentrations of 6%, 10%, and 14%. Cream evaluation includes organoleptic aspects, cream type, spreadability, pH, viscosity, and physical stability testing. The research findings show that creams containing cashew leaf extract at different concentrations and stored for 4 weeks at room temperature, low temperature, and 40°C demonstrate relatively stable physical stability. Statistical analysis has been conducted on the evaluation results, and the findings will be discussed in detail. This research concludes that cashew leaf extract cream formulations exhibit good physical stability during the tested storage period. These findings provide a better understanding of the formulation and stability of creams containing cashew leaf extract, which can serve as a basis for the development of more effective and stable pharmaceutical products in the future.